Cognitive Bias on Financial Decision-Making in MSMEs - Purnamasari, Imas; Sugiharti, Harpa; Machmud, Amir; Hartika, Nely; Ahiase, Godwin; Acheampong, Kennedy (Faculty of Economics and Business Universitas Jenderal Soedirman, 2025)
This study aims to analyze the effect of cognitive bias on the Financial Decision Making of MSME actors in Bandung City. The research method used is descriptive verification with quantitative approach. Data were collected through questionnaires distributed to 385 MSME actors in Bandung City. The variables being studied for independent variables are overconfidence bias, confirmation bias, herding bias, anchoring bias, hindsight bias, the illusion of control bias, loss aversion bias, endowment bias, regret aversion bias, and status quo bias, while for the dependent variable is Financial Decision Making. Regression results show that overconfidence bias and loss aversion bias positively affect financial decision-making, while the illusion of control bias has a negative effect. Other cognitive bias variables do not affect Financial Decision Making. Cognitive biases that cause suboptimal financial decisions can hinder the productivity of MSMEs, this can affect the contribution of the MSME sector to the National Gross Domestic Product.